Training on Strengthening Teacher’s Personality at SMK Lab Business School, Tangerang to Improve Learning Quality - Khusaini Khusaini; Bambang Mardisentosa; Hudaya Latuconsina (Jurnal Pemberdayaan Masyarakat Madani (JPMM), 2020)
Teacher personality competence must be continuously improved in order to support a good quality of learning in the classroom. This training activity aims to strengthen the teacher's personality competence, to find out participants’ perception of training, and the level of learning quality. This activity was attended by 38 participats of SMK Lab Business School, Tangerang. The training methods used in this study were direct teaching, discussion, brain storming, and assignments. The results of the PKM implementation as measured by facilities, materials, methods, instructors, and organizers show that the training could run well and smoothly with participant responses in good category. In addition, participants felt very satisfied. The teachers considered that there was an increase in knowledge and competencies. The results of the post-PKM monitoring show that the teacher’s quality, using three dimensions of learning quality: classroom management, student support, and cognitive activation, was in good categories; although there were still some indicators that must be corrected by the teachers. Therefore, the results of this activity recommend that schools can carry out similar activities to strengthen the competencies of other teachers. The learning quality should always be maintained by teacher, so that the learning objectives can be achieved properly.